The effect of a wearable soft-robotic glove on motor function and functional performance of older adults. Issue 1 (2nd January 2020) - Radder, Bob; Prange-Lasonder, Gerdienke B.; Kottink, Anke I.R.; Holmberg, Johnny; Sletta, Kristin; Van Dijk, Manon; Meyer, Thomas; Buurke, Jaap H.; Rietman, Johan S.
ABSTRACT: Reduced grip strength, resulting in difficulties in performing daily activities, is a common problem in the population of older adults. Newly developed soft-robotic devices have the potential to support older adults with reduced grip in daily activities. The objective of this study was to evaluate the direct, assistive effect of grip support from the wearable, soft-robotic ironHand glove. In total, 65 older adults with self-reported decline of hand function resulting from various disorders participated in this cross-sectional study. They performed various hand function tests with and without the glove during a single session. At the end, usability was scored. Participants were able to produce more pinch strength with the glove compared to without glove ( p ≤ 0.001) and usability was rated very positively. However, this was not reflected in improved functional performance with the glove, as measured with timed tasks ( p < 0.001). Furthermore, no correlation was found between baseline handgrip strength and changes in performance (between without and with glove) of all assessments ( ρ ≤ 0.137, p ≥ 0.288). Further design adaptations are desired and more research is needed to investigate if performance with the glove can improve, when taking quality of task performance into account, or when applying a longer acquaintance period with the glove.